Preparation method and application of temperature-sensitive phase-change plugging agent

By using temperature-sensitive phase-transformed sealant in shale gas drilling fluid, the problem of water-based drilling fluid causing instability of the well wall is solved, and the hydration and expansion of shale at different temperatures is effectively suppressed and the well wall is improved. Stability, reducing the difficulty and cost of drilling fluid preparation.

CN116218487BActive Publication Date: 2025-02-18SINOPEK PETROLEUM IZHINIRING TECH SERVIS KO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211673379.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-02-18
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

In shale gas drilling, water-based drilling fluid leads to instability of the well wall after entering the mud shale formation. The performance of existing sealant changes greatly at different temperatures, which increases the difficulty and cost of preparing drilling fluid.

Method used

The temperature-sensitive phase-transformed sealing agent was prepared by reverse phase suspension polymerization. N-ethyl methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and VTMS-SiO2 were used as raw materials to pass the temperature The response achieves phase change, thereby effectively inhibiting the hydration and expansion of shale at different formation temperatures.

Benefits of technology

It can effectively suppress the hydration and expansion of shale at different formation temperatures, improve the stability of the well wall, and reduce the difficulty and cost of drilling fluid preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116218487B_ABST
    Figure CN116218487B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of drilling technology, and in particular to a preparation method and application of a temperature-sensitive phase-change plugging agent. The plugging agent is prepared by reverse suspension polymerization using N-ethyl methacrylamide, 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid and vinyl trimethoxysilane surface-modified silica as raw materials. It has both the bridging effect of nanoparticles and the deformation ability of organic particles, and can undergo phase change with temperature, thereby playing a dual role of physical plugging and chemical inhibition at the same time, achieving the effect of effectively inhibiting the hydration expansion of shale at different formation temperatures and improving the stability of the well wall.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of drilling, and in particular to a preparation method and application of a temperature-sensitive phase-change plugging agent. Background Art

[0002] Shale gas is an unconventional oil and gas developed in organic-rich shale formations with a large number of micro-nano pores. It is a type of natural gas reservoir and exists in both free and adsorbed states. It is a relatively clean, low-pollution, low-priced unconventional natural gas resource with great development and utilization value.

[0003] At present, oil-based drilling fluids with good inhibition and strong lubricity are used in shale gas drilling in my country. However, due to the disadvantages of high cost and high pollution of oil-based drilling fluids, water-based drilling fluids with less pollution, strong self-cleaning ability, low drilling cost and environmental friendliness have been favored by researchers.

[0004] However, since shale formations have many micropores, when water-based drilling fluid enters the formation, the water in it and some of the lost water enter the rock formation through the cracks and pores, causing the clay or shale rock minerals to hydrate and expand, and then causing the well wall to become instable. This has seriously restricted the progress of shale gas exploration and production technology in my country.

[0005] Adding plugging agents to the drilling fluid system can seal the micro voids in the shale layer and avoid well wall instability. However, in the drilling fluid system, the suspension properties and rheological properties of bentonite particles are easily affected by the ambient temperature (formation temperature). During the drilling process, the viscosity of the drilling fluid changes greatly with the increase in temperature. Usually, a variety of plugging materials need to be prepared to meet the needs of drilling in formations at different temperatures, which increases the difficulty of drilling fluid preparation and drilling costs. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies in the background technology and provide a temperature-sensitive phase-change plugging agent that can undergo phase change with temperature.

[0007] The objective of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a temperature-sensitive phase-change plugging agent, comprising: using N-ethyl methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and VTMS-SiO 2 It is prepared by reverse suspension polymerization.

[0009] Further, the method specifically includes the following steps:

[0010] S1. Take the N-ethyl methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and VTMS-SiO 2Dissolve in deionized water and disperse evenly to obtain a mixed system;

[0011] S2. Add a crosslinking agent and an initiator to the mixed system in sequence and stir evenly;

[0012] S3. Raise the temperature to 55-75°C under a protective gas atmosphere and react for 4-6 hours to obtain the product.

[0013] Furthermore, the method further comprises the following steps:

[0014] S4. Washing, drying and crushing the product to obtain the temperature-sensitive phase-change plugging agent.

[0015] Furthermore, the VTMS-SiO 2 The VTMS-SiO 2 The preparation method comprises the following steps:

[0016] S5. The dried nano-silica powder is dispersed in an ethanol solution having a pH value of 4-5 and subjected to ultrasonic treatment for 30-60 min;

[0017] S6. Adding vinyltrimethoxysilane to the ethanol solution, and then ultrasonically treating for 50-70 min to obtain a mixed solution;

[0018] S7. The mixed solution is heated to 70-85° C. under a protective gas atmosphere for 4-6 hours, with continuous stirring during the reaction to obtain a modified product;

[0019] S8. Washing, centrifuging, drying and crushing the modified product to obtain the VTMS-SiO 2 powder.

[0020] Furthermore, in step S1, the N-ethyl methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, VTMS-SiO 2 The weight ratio of iodine to deionized water is 20-30:5-10:3-6:1-2:120-140.

[0021] Furthermore, in step S2, the crosslinking agent is N,N-methylenebisacrylamide, the initiator is ammonium persulfate, the amount of the crosslinking agent added is 0.2-0.4% of the total mass of the monomers, and the amount of the initiator added is 0.3-0.6% of the total mass of the monomers.

[0022] Further, the monomers are N-ethyl methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and VTMS-SiO 2 .

[0023] Furthermore, in steps S3 and S7, the protective gas may be nitrogen or an inert gas.

[0024] Furthermore, in step S4, the washing may be performed with deionized water for 3-4 times, and the drying may be performed by freeze drying for 2-3 days. There is no special requirement for the particle size of the product after pulverization, as long as it meets the requirements of the drilling fluid.

[0025] Furthermore, in step S5, the concentration of the ethanol solution is 73%-78%, the frequency of the ultrasonic treatment is 40kHz, the nano-silicon dioxide can be vacuum dried at 120°C for 24 hours, and the pH value of the ethanol solution can be adjusted by dilute hydrochloric acid, dilute sulfuric acid, or phosphoric acid.

[0026] Furthermore, in step S6, the amount of vinyltrimethoxysilane added is 18-25% of the mass of the nano-silicon dioxide, and the frequency of ultrasonic treatment is 40 kHz.

[0027] Furthermore, in step S8, the washing is generally performed with anhydrous ethanol, washed 3-4 times, centrifuged 4-5 times, and dried in an oven at 70° C. to constant weight, and the particle size of the product after crushing is ensured to be fine enough.

[0028] The present invention also provides a temperature-sensitive phase-change plugging agent obtained by a preparation method of the temperature-sensitive phase-change plugging agent.

[0029] The invention provides an application of a temperature-sensitive phase-change plugging agent as a drilling fluid additive.

[0030] Furthermore, the added amount is 0.5-1.0 wt%.

[0031] The temperature-sensitive phase-change plugging agent prepared by the present invention uses N-ethylmethacrylamide (NEMAM) as a temperature-sensitive material in terms of raw material selection. NEMAM has both hydrophilic amide groups and hydrophobic ethyl and methyl groups, and thus has a lower critical solution temperature (LCST); in addition, 2-acrylamide-2-methylpropanesulfonic acid (AMPS) contains a sulfonic acid group, which can enhance the high-temperature stability of the polymer; acrylic acid (AA) is an anionic monomer, which has hydrophilicity due to the presence of a carboxyl group, and the introduction of a hydrophilic monomer can increase the phase change temperature of the temperature-sensitive monomer to a certain extent.

[0032] The present invention adopts vinyl trimethoxy silane (VTMS) to modify nano-SiO 2 , nano-SiO 2 There are different forms of hydroxyl groups on the surface, and some of them react with the silane coupling agent VTMS in water. 2 That is, it inherits the advantages of inorganic silica, and the presence of VTMS significantly reduces the 2The median particle size of the nanoparticles is such that the nanoparticles have double bonds on their surface and are reactive, which can improve their dispersibility in water-based drilling fluids.

[0033] The beneficial effects of the present invention are:

[0034] The temperature-sensitive phase-change plugging agent prepared by the present invention combines environmentally responsive polymers with inorganic nanoparticles to realize the intelligence of the material, and at the same time has the bridging effect of nanoparticles and the deformation ability of organic particles, and can undergo phase change with temperature. When the bottom temperature is lower than the LCST temperature, the temperature-sensitive plugging agent forms strong hydrogen bonds with surrounding water molecules to show hydrophilicity, enters microcracks under pressure, and forms a physical plugging layer by filling, bridging, etc.; when the formation temperature is higher than the LCST, the temperature-sensitive plugging agent is dominated by the hydrophobic association of non-polar ethyl and methyl groups due to the destruction of hydrogen bonds, and the molecular chain shows hydrophobicity, and the chain changes from a linear stretching state to a curled contraction state, precipitates from the solution, and forms a hydrophobic film on the surface of the physical plugging layer, which plays a role of chemical inhibition, and achieves the effect of effectively inhibiting the hydration expansion of shale at different formation temperatures and improving the stability of the well wall. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The microscopic morphology of the base mud cake before and after treatment with the temperature-sensitive phase-change plugging agent;

[0036] Figure 2 The contact angle of the base slurry cake before and after treatment with the temperature-sensitive phase-change plugging agent;

[0037] Figure 3 The curve of light transmittance of the temperature-sensitive phase-change plugging agent changing with wavelength and temperature;

[0038] Figure 4 This is a working principle diagram of the temperature-sensitive phase-change plugging agent;

[0039] Figure 5 Schematic diagram of the phase change of the thermosensitive monomer NEMAM with temperature. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following.

[0041] Example 1: Preparation of drilling fluid

[0042] Based on practical experience, the formula of drilling fluid is as follows: 3wt% bentonite, anhydrous sodium carbonate (NaCO 3 ) 0.2wt%, potassium chloride 5wt%, zwitterionic polymer coating agent (FA367) 2wt%, sulfonated lignite resin (SPNH) 1wt%.

[0043] First, a base slurry with a mass ratio of deionized water, bentonite and anhydrous sodium carbonate of 100:3:0.2 was prepared, and after being fully stirred at a speed of 2000r / min, it was allowed to stand at room temperature for hydration for 24 hours to obtain a bentonite base slurry. Then, potassium chloride, zwitterionic polymer coating agent and sulfonated lignite resin in the formula were added in order, and stirred at a speed of 2000r / min to obtain the basic drilling fluid required for the experiment.

[0044] Example 2: VTMS-SiO 2 Preparation

[0045] In this experiment, VTMS was used to 2 Surface modification was performed. 30 g of nano-SiO 2 The powder was dried in a vacuum oven at 120°C for 24 h. A 75% ethanol solution was prepared in a beaker and the pH value was adjusted to 4 with dilute hydrochloric acid. 2 The powder was dispersed in the mixed solution and treated with ultrasound at 40 kHz for 30 min. Then, 6 g of VTMS was dissolved in the mixed solution, treated with ultrasound for 1 h, and then transferred to a three-necked flask. The reaction was heated to 85 °C and heated under N 2 The mixture was stirred continuously for 6 h under the atmosphere. After the reaction was completed, the product was washed with anhydrous ethanol for 3 times, centrifuged repeatedly for 4 times, and then dried in an oven at 70 °C to constant weight. The modified VTMS-SiO 2 Powder 23.4g.

[0046] Example 3: Temperature-sensitive phase-change plugging agent (P(NEMAM-AMPS-AA) / VTMS-SiO 2 )

[0047] 75 g N-ethylmethacrylamide, 27 g 2-acrylamide-2-methylpropanesulfonic acid, 10 g acrylic acid, and 5 g VTMS-SiO 2 The powder was dissolved in deionized water. After stirring and dispersing for 30 minutes, 0.5 g of N,N-methylenebisacrylamide was added, and then 3.5 g of 20% ammonium persulfate solution was slowly added. After the system was quickly stirred and uniformly mixed, 2 The reaction was carried out at 70 °C for 4 h under atmosphere protection. After the reaction was completed, the product was washed with deionized water for 3 times, freeze-dried for 2 days, and crushed to obtain a powder sample P(NEMAM-AMPS-AA) / VTMS-SiO 2 88.92g, which is the temperature-sensitive phase-change plugging agent.

[0048] Microstructure analysis before and after treatment with temperature-sensitive phase change plugging agent:

[0049] Figure 1 The mud cake obtained by API filtration (normal temperature and medium pressure filtration) of base mud (basic drilling fluid) (Figures a and b) and the mud cake containing 0.8% temperature-sensitive plugging agent P (NEMAM-AMPS-AA) / VTMS-SiO 2 The surface morphology of the mud cake (Figures c and d) obtained by filtration of the base slurry under high temperature and high pressure (130℃, 4.5MPa).

[0050] It can be seen that when no plugging agent is added to the base slurry, holes, cracks and wrinkles exist on the filter cake formed by filtration at room temperature and medium pressure. After adding the thermosensitive plugging agent prepared by the present invention, even under high temperature and high pressure, the surface of the mud cake is densely combined and has a relatively smooth film.

[0051] Analysis of contact angle of base slurry cake before and after treatment with temperature-sensitive phase change plugging agent:

[0052] Figure 2 Schematic diagram of the contact angle of the base slurry mud cake before and after treatment with the thermosensitive phase change plugging agent, where (a) represents the mud cake obtained from the base slurry at room temperature, (b) represents the mud cake obtained from the base slurry containing 0.8% thermosensitive plugging agent at room temperature, and (c) represents the mud cake obtained from the base slurry containing 0.8% thermosensitive plugging agent at 130°C.

[0053] It can be seen that before the product of the present invention is added, the contact angle of the mud cake is 0°. After adding 0.8% of the product of the present invention, the contact angle of the mud cake is 40°. After the temperature is raised to 130°C, the contact angle becomes 128°, which indicates that the thermosensitive plugging agent undergoes a phase change at high temperature, the molecular chain becomes hydrophobic, and the wettability is reversed on the mud cake surface, thereby improving the inhibition ability to clay.

[0054] Analysis of temperature response behavior of temperature-sensitive phase change plugging agent:

[0055] The transmittance of the product prepared by the present invention at different temperatures (wavelength λ = 200-800nm) was tested to determine the temperature response behavior of the polymer. The results are as follows Figure 3 shown.

[0056] The fully swollen thermosensitive phase change plugging agent hydrogel sample is placed in a cuvette, and the transmittance of the sample at different temperatures (40-130°C) as a function of wavelength is measured by a UV-visible spectrophotometer connected to a thermostatic bath to study the temperature responsiveness of the thermosensitive plugging agent. After placing the thermosensitive sample in the cuvette, it is heated by a temperature sensor, and after setting the temperature range, the air is tested as the background first, and then the transmittance of the sample is tested.

[0057] It can be seen that with the increase of wavelength, the transmittance of the material shows an overall increasing trend and tends to be stable near the wavelength of 420nm; with the increase of temperature, the transmittance of the material decreases. When the temperature is 40℃, the transmittance of the material is about 70.488%. When the temperature rises to 130℃, the transmittance drops sharply to 37.879%. This phenomenon shows that P(NEMAM-AMPS-AA) / VTMS-SiO 2 The material has sensitive temperature response behavior.

[0058] Routine performance evaluation of drilling fluid:

[0059] The drilling fluid properties were evaluated according to the American Petroleum Institute (API) test protocol. First, the room temperature fluid loss (FLAPI) of the drilling fluid before and after aging at 130°C was evaluated using a medium pressure mud filter (7NS-2A, Qingdao Tongchun Petroleum Instrument Co., Ltd., China) for 30 min. The high temperature and high pressure fluid loss (FLAPI) of the polymer-based slurry after aging at 130°C for 16 h was determined using a high temperature and high pressure filter (GGS42-2A, Qingdao Hengtaida Electromechanical Equipment Co., Ltd.). FLAPI and FLAPI were measured at 25°C and 0.7 MPa and 130°C and 4.5 MPa, respectively.

[0060] The room temperature rheological properties of the drilling fluid before and after aging at 130°C for 16 hours were measured using a six-speed rotational viscometer (ZNN-D6B). The surface viscosity AV (mPa·s), plastic viscosity PV\left (mPa·s) and yield point YP (Pa) were measured at 300rpm and 600rpm, respectively. The formula used is as follows:

[0061] AV=1 / 2Ф600(mPa·s)

[0062] PV=Φ600-Φ300(mPa·s)

[0063] YP=1 / 2(Φ300-PV)(Pa)

[0064] in, and These are the speed readings of a six-speed rotational viscometer at 300 rpm and 600 rpm respectively.

[0065] The conventional properties of the basic drilling fluid before and after treatment with 0.8% of the plugging agent prepared by the present invention are shown in Table 1.

[0066] Table 1

[0067]

[0068]

[0069] It can be seen from Table 1 that the drilling fluid added with the product of the present invention has a FL API and FL HTHP130℃ Both are lower than the basic drilling fluid and have a certain effect of reducing filtration loss.

[0070] Evaluation of plugging performance of drilling fluid system:

[0071] In order to further determine the plugging performance of the temperature-sensitive phase-change plugging agent, a core displacement evaluation experiment was conducted. The core displacement device uses an artificial core to simulate the permeability and filtration loss of the core under formation pressure and temperature conditions.

[0072] The test process is as follows:

[0073] (1) According to the configuration of the drilling fluid formula of Example 1, 1# (basic drilling fluid), 2# (basic drilling fluid with 0.5% of the product of the present invention added), and 3# (basic drilling fluid with 0.8% of the product of the present invention added) were respectively configured. The configured drilling fluid system was canned and heat-aged at 130°C for 16 hours;

[0074] (2) Conducting gas permeability test on the prepared core;

[0075] (3) After the gas permeability test is completed, the drilling fluid system is loaded and the system area is used. During the displacement process, the confining pressure is kept about 3.5 MPa higher than the displacement pressure, and the formation temperature is simulated at 130°C. After the artificial core is contaminated for 30 minutes, the system displacement permeability is calculated to evaluate the plugging situation.

[0076] Its plugging performance is shown in Table 2:

[0077] Table 2

[0078] Displacement medium <![CDATA[Pre - pollution permeability 10 -3 mD]]> <![CDATA[Permeability after contamination 10 -3 mD]]> Permeability reduction value (%) 1# 38.6 3.672 90.49 2# 26.4 0.2294 99.13 3# 18.2 0.08137 99.55

[0079] It can be seen that the plugging efficiency of the drilling fluid system is improved after adding the plugging agent prepared by the present invention. 2 ) The drilling fluid system has the highest plugging efficiency and obvious plugging effect, with the permeability reduction value increased from 90.49% to 99.55%.

[0080] Comparative Example 1

[0081] According to the literature (Wang Weiji, Qiu Zhengsong, Zhong Hanyi, Huang Weian, Zhao Xin, Dong Bingqiang, Bao Dan. Shale reservoir temperature-sensitive P (NIPAm-co-AA) / nano-SiO 2Preparation and properties of composite plugging agent[J]. Acta Petrolei Sinica, 2015, 36(03): 378-384.) The temperature-sensitive P(NIPAm-co-AA) / nano-SiO 2 The composite plugging agent was tested for its plugging performance. The test method was the same as that for the product of the present invention, and the test results are shown in Table 3 below: (where 4# represents the basic drilling fluid with 0.5% temperature-sensitive P(NIPAm-co-AA) / nano-SiO 2 Composite plugging agent, 5# means basic drilling fluid with 0.8% temperature-sensitive P(NIPAm-co-AA) / nano-SiO 2 Composite plugging agent

[0082] Table 3

[0083] Displacement medium <![CDATA[Pre-pollution permeability 10 -3 mD]]> <![CDATA[Permeability after contamination 10 -3 mD]]> Permeability reduction value (%) 1# 38.6 3.672 90.49 4# 28.7 0.2671 99.06 5# 23.1 0.1174 99.49

[0084] By comparison, it can be seen that under the condition of the same addition amount, the product P(NEMAM-AMPS-AA) / VTMS-SiO2 temperature-sensitive phase change plugging agent of the present invention has a lower permeability than the P(NIPAm-co-AA) / nano-SiO2 composite plugging agent both before and after pollution, and the permeability reduction value is higher than the P(NIPAm-co-AA) / nano-SiO2 composite plugging agent, and has better plugging performance.

[0085] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a temperature-sensitive phase-change plugging agent, characterized in that: The product was prepared by reverse suspension polymerization with N-ethylmethacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and VTMS-SiO2 as raw materials. The specific steps include: S1. Take the N-ethyl methacrylamide, 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid and VTMS-SiO2 dissolved in deionized water and dispersed evenly to obtain a mixed system; S2. sequentially adding a crosslinking agent and an initiator to the mixed system and stirring evenly; S3. Raise the temperature to 55-75°C under a protective gas atmosphere and react for 4-6h to obtain a product; In step S1, the weight ratio of N-ethyl methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, VTMS-SiO2 and deionized water is 20-30:5-10:3-6:1-2:120-140.

2. The method for preparing a temperature-sensitive phase-change plugging agent according to claim 1, characterized in that: The following steps are also included: S4. Washing, drying and crushing the product to obtain the temperature-sensitive phase-change plugging agent.

3. The method for preparing a temperature-sensitive phase-change plugging agent according to claim 1, characterized in that: The VTMS-SiO2 is silicon dioxide surface-modified by vinyltrimethoxysilane, and the preparation method of the VTMS-SiO2 comprises the following steps: S5. The dried nano-silica powder was dispersed in an ethanol solution having a pH value of 4-5 and subjected to ultrasonic treatment for 30-60min; S6. Vinyltrimethoxysilane was added to the ethanol solution, and then ultrasonically treated for 50-70min to obtain a mixed solution; S7. The mixed solution is heated to 70-85° C. under a protective gas atmosphere for 4-6 hours, with continuous stirring during the reaction to obtain a modified product; S8. The modified product is washed, centrifuged, dried and pulverized to obtain the VTMS-SiO2 powder.

4. The method for preparing a temperature-sensitive phase-change plugging agent according to claim 1, characterized in that: In step S2, the crosslinking agent is N,N-methylenebisacrylamide, the initiator is ammonium persulfate, the amount of the crosslinking agent added is 0.2-0.4% of the total mass of the monomers, and the amount of the initiator added is 0.3-0.6% of the total mass of the monomers.

5. The method for preparing a temperature-sensitive phase-change plugging agent according to claim 3, characterized in that: In step S5, the concentration of the ethanol solution is 73%-78%, and the frequency of ultrasonic treatment is 40kHz; And / or, in step S6, the amount of vinyltrimethoxysilane added is 18-25% of the mass of the nano-silicon dioxide, and the frequency of ultrasonic treatment is 40 kHz.

6. A temperature-sensitive phase-change plugging agent obtained by the preparation method of a temperature-sensitive phase-change plugging agent according to any one of claims 1 to 5.

7. Use of the temperature-sensitive phase-change plugging agent according to claim 6 as a drilling fluid additive.

8. The use of a temperature-sensitive phase-change plugging agent as a drilling fluid additive according to claim 7, characterized in that: The addition amount is 0.5-1.0wt%.

Citation Information

Patent Citations

  • Temperature-sensitive-type intelligent nano particles used in drilling fluid and preparation method thereof

    CN105038728A

  • Polymer nanometer blocking agent for water-based drilling fluid and its preparation method

    CN107915798A